Characterization of hyperimmune anti-human serum produced in sheep - Jessica Ocalia Solana Rodríguez; Laura María Reyes Díaz; Victoria Esther Gonzalez Ramírez; Miriam San Juan Bosco Lastre González; Yusnaby Borrego González; Martha Leonor Paradoa Pérez; Irma Vega García; Raúl Ramos Pupo; Oliver Pérez (Universidad de Ciencias Médicas de La Habana, 2020)
Introduction: Immunoelectrophoresis is a precipitation technique that allows the characterization of complex biological samples. The Immunology Department of the Institute of Basic and Pre-Clinical Sciences "Victoria de Girón" has a hyperimmune antiserum obtained by immunization of sheep against human serum total proteins and it also has an anti-human IgA antiserum obtained from human colostrum. Objective: The aim of this study was to identify IgG, IgM and IgA in human serum and to determine response to anti-human IgM in human colostral IgA with antiserum obtained in sheep. Material and Methods. An observational descriptive cross-sectional study was conducted from November 2017 to June 2018. Immunoelectrophoresis of normal human serum was performed using hyperimmune antiserum. Results: These procedures allowed to identify IgG, IgM and IgA in addition to albumin and other protein fractions and to determine response to anti-human IgM in human colostral IgA with antiserum obtained in sheep. Conclusions: This work allowed us to identify and determine significant anti-class responses of immunoglobulins in the sample studied.